SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS FOR ENHANCING VISUAL ARTS LESSONS IN GENERAL EDUCATION SCHOOLS - Ibrohimova Zebuniso Nodir qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This article explores the issues of improving visual arts lessons in general education schools through a new scientific and methodological approach. It presents theoretical and practical foundations for integrating didactic methods, applying interactive and innovative technologies in the learning process, and identifying criteria for assessing art competence.